Performance and emission analysis of a Komatsu PC195LC common-rail diesel engine under injector type and spray-angle variations - Yosephus Ardean Kurnianto Prayitno; Sugiyanto Sugiyanto; Ilham Ayu Putri Pratiwi; Braam Delfian Prihadianto; Muhammad Fauzan; Setyawan Adi Nugraha; Josua Aditya Manuel; Sutikno Sutikno; Muhammad Novan Budi Prasetya (Politeknik Negeri Lhokseumawe, 2026)
Injector condition and spray characteristics strongly influence fuel atomization, combustion efficiency, and exhaust emissions in common-rail diesel engines. This study aims to evaluate the performance and emission responses of a Komatsu PC195LC diesel engine under variations in injector type and spray angle by integrating field measurements with bench-scale spray characterization. Two injector types (OEM vs local) were tested at 1050, 1500, and 2050 rpm; fuel rate and specific fuel consumption were logged over two-minute windows, and post-operation (3000 h) inspections assessed wear. A back-lit imaging rig measured spray angle and droplet distribution at 50 and 100 bar; a simple mixing–atomization model linked spray metrics to air–fuel preparation. Field results show the OEM injector reduced fuel rate by 0.78 L/h (3.45%) versus the local unit under the duty cycle tested. Bench data indicate wider spray angles and finer droplets at higher pressure, consistent with improved mixture formation. Joint analysis attributes the observed SFC gains to healthier nozzle geometry and spray targeting. The study provides guidance on injector selection, condition monitoring, and pressure/angle calibration towards Euro-4-aligned efficiency and emissions.